A NOVEL OCTAHEDRAL NIOBIUM OXYCHLORIDE CLUSTER BUILT FROM INTERCONNECTED Nb6Cl12O4 UNITS: Cs2Sc3Nb12 - Fakhili Gulo (Indonesian Journal of Chemistry, 2011)
A novel octahedral niobium cluster oxychloride compound, Cs2Sc3Nb12Cl27O8 was synthesized by solid-state route techniques from stoichiometric mixture of CsCl, Sc2O3, Nb, NbCl5, and Nb2O5, heated at 700 °C for two days. The crystal structure was determined by single crystal X-ray diffraction method. It crystallizes in orthorhombic system with space group of Pnma, a = 17.5206(1) Å, b = 29.6899(3) Å, c = 9.2114(1) Å, and V = 4791.63(8) Å3. The structure is based on  unit in which four oxygen ligands selectively occupy inner positions arranged in sets of three and one on opposite side of the Nb6 octahedron. Each cluster shares three apical-chlorine ligands with three adjacent clusters to form layers with topology similar to that of graphite. The cluster units are also connected to each other by both cesium and scandium atoms to form a three-dimensional framework. This compound exhibits 14 valence electrons per cluster.